Pengembangan Aplikasi Pembelajaran Pemrograman Menggunakan Model Agile Development - Teti Desyani; Achmad Fahmi Respati; Dhimas Marwahyu; Maharizal Ilham Farabi; Muhammad Andinun; Irpan Kusyadi (Jurnal Informatika Universitas Pamulang, 2022)
Academic technology can be understood as a complicated and based technique that involves human beings, strategies, ideas, gear, and organizations to analyze troubles, discover approaches to remedy issues, put in force, verify, control problem solving that covers all components of human studying. In the back of the various learnings about pemrograman, it's miles necessary to create a website that offers getting to know about pemrograman, from records, substances, to creating the application itself. Internet site software development is made the use of the Agile improvement version technique, that's a way so as to begin again from the start after the application is completed. Packages which have been completed to the review stage will return to the planning stage by using accumulating records and feedback from users to eventually redevelop the application by adding numerous features to be able to make the website even higher.